2015
DOI: 10.1098/rspb.2015.1063
|View full text |Cite
|
Sign up to set email alerts
|

Population-specific responses to an invasive species

Abstract: Predicting the impacts of non-native species remains a challenge. As populations of a species are genetically and phenotypically variable, the impact of non-native species on local taxa could crucially depend on populationspecific traits and adaptations of both native and non-native species. Bitterling fishes are brood parasites of unionid mussels and unionid mussels produce larvae that parasitize fishes. We used common garden experiments to measure three key elements in the bitterling-mussel association among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 43 publications
(83 reference statements)
3
33
0
Order By: Relevance
“…While populations from Central Poland were used by R. amarus for oviposition, with all bitterling embryos later ejected, S. woodiana populations from the southern Czech Republic were completely avoided by R. amarus , thereby mitigating the costs of failed development. Hence, the identity of S. woodiana populations determines the impact of S. woodiana on native R. amarus , from almost neutral to highly negative (Reichard, Vrtílek, Douda, & Smith, ; Reichard et al., ). The current study demonstrated that the two S. woodiana populations previously used to test their response to bitterling fish are genetically differentiated (PLLI and CZKY populations, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While populations from Central Poland were used by R. amarus for oviposition, with all bitterling embryos later ejected, S. woodiana populations from the southern Czech Republic were completely avoided by R. amarus , thereby mitigating the costs of failed development. Hence, the identity of S. woodiana populations determines the impact of S. woodiana on native R. amarus , from almost neutral to highly negative (Reichard, Vrtílek, Douda, & Smith, ; Reichard et al., ). The current study demonstrated that the two S. woodiana populations previously used to test their response to bitterling fish are genetically differentiated (PLLI and CZKY populations, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…However, S. woodiana started to spread in the first decade of the 21st Century (Lajtner & Crnčan, ) and its populations are now recorded from much colder habitats, including subalpine lakes in northern Italy (2010) (Kamburska, Lauceri, & Riccardi, ) and regions that are subject to relatively long winters (southern Sweden in 2005) (Svensson & Ekström, ). At least two European populations of S. woodiana possess separate morphotypes on the basis of their shell shape, with a distinct coevolutionarily driven response to a parasitic fish in Europe (Reichard et al., ). A recent study of two Italian S. woodiana populations demonstrated that the two morphotypes are not genetically distinct at a mitochondrial marker (Guarneri et al., ), suggesting that morphological variability of S. woodiana populations in Europe represents a plastic response to environmental conditions (a common feature of unionid mussels) rather than genetically determined variability (Soroka & Zdanowski, ).…”
Section: Introductionmentioning
confidence: 99%
“…This information is also relevant for the delimitation of freshwater mussel's conservation units (Douda et al., ). It has only been recently demonstrated that fish–glochidia relationships can vary both between geographically distinct lineages of species and within these lineages also contrasting histories of sympatry (Reichard et al., ). This illustrates the inherent difficulty in ensuring the quality of host resources for freshwater mussels at species level because population‐specific attributes arising from local adaptation and fine‐scale coevolutionary dynamics can play a significant role in host compatibility.…”
Section: Future Directionsmentioning
confidence: 99%
“…Therefore, some specialist mussels may have a “bet‐hedging” strategy producing batches of glochidia with reduced fitness in their typical conditions (regular host) in exchange for increased fitness in stressful conditions (alternative host). From an evolutionary perspective, this can be an important advantage, and it has been already documented that female individuals within a population differ in their compatibility with different fish host species (Douda et al., ; Reichard et al., ). Some studies with other faunal groups already addressed this “bet‐hedging” strategy (Jones, Patel, Levy, Storeygard, & Balk, ; Smith & Bernatchez, ; Woolhouse, Haydon, & Antia, ; Zaffarano, McDonald, & Linde, ), but our knowledge on the potential presence of bet‐hedging strategy and evolution of host specificity in mussels is limited.…”
Section: Future Directionsmentioning
confidence: 99%
“…Data collected in its native range, in contrast, illustrate that there are differences in host quality (Dudgeon & Morton, ; Hua, Xu, & Wen, ). Moreover, data from non‐native S. woodiana indicate population‐specific variability in host compatibility with one host species, the European bitterling ( Rhodeus amarus ), corresponding with the contrasting histories of recent sympatry between R. amarus and S. woodiana at the population level (Reichard et al., ).…”
Section: Introductionmentioning
confidence: 99%